Convenient Methods to Access Chiral Camphanyl Amine Derivatives by Sodium Borohydride Reduction of d-(–)-Camphorquinone Imines - Periasamy, Mariappan; Sanjeevakumar, Nalluri; Obula Reddy, Polimera (Synthesis, 2012)
d-(–)-Camphorquinone imines prepared using methanolic ammonia, ethanol amine, exo-(–)-bornylamine, ethylene diamine, propylene diamine, and trans-(R,R)-1,2-diaminocyclohexane, upon reduction using sodium borohydride in methanol, give the corresponding chiral exo amino alcohol and diamine derivatives in good yields (75–95%).
Keywords: sodium borohydride; chirality; reduction; diimines; diamines